New Reachable Horizons in the Fritz Jahr's Bioethical Imperative - Jayapaul Azariah Azariah (European Journal of Bioethics, 2017)
The present paper traces the scientific and Christian theological climate that led to the coining of the new word â€œ bioethics â€ by the German Christian pastor Rev. Fritz Jahr in 1926. Miller and Professor Hans-Martin Sassâ€™s English translation of Rev. Jahrâ€™s works were used. There are a total of 22 Rev. Jahrâ€™s thought-provoking original articles which were grouped into four major categories: (i) Ethics and Bioethics (ii) Radical Christian Theology and Bioethical Imperatives (iii) Sexual Ethics and (iv) Philosophy of Life and Death. Coining of the word â€œbiotechnologyâ€ in 1917 precedes the word bioethics by ten years. The paper details significant advancement in science as well as the rise of moral issues. Significantly, within a short span of 10 years the influence of the power of science was such that the moral-width of Rev. Jahrâ€™s society began to shrink to that extent that it disturbed him to coin a new word â€œBioethicsâ€ to counter-balance the fast moral degradation. Rev. Jahr identified three contributing factors for moral defacement. Steinachâ€™s gonad transplant experiments and Theologian F.D.E. Schleiermacherâ€™s radical views of Christianity may have caused the moral crisis in his society resulting in the prevalence of syphilis. Jahrâ€™s threefold bioethical imperative model of â€“ Life, value and education â€“ has been considered. A new educational policy of Life Oriented Value Education (love) has been suggested so as to revive social and moral values